A imaginação no terceiro gênero de conhecimento em Spinoza - Mathias Netto, Jayme (2014)
Our aim, with this work, is emphasize the problem of imagination in the third kind of knowledge in the work Ethics by Benedictus de Spinoza (1632-1677). In part II of Ethics, the author explicits the three kinds of knowledge: the imagination (the first kind), the reason (the second kind) and the intuitive science (the third). Our conjecture is that there is an interaction between the first and the third kinds and that this occurs as follows: (1) by the Spinoza’s preoccupation in use the imagination so that the mind links the external things to the ontological context of immanence. And (2) by the inevitability of linguistic signals (while part of imagination), without which the power of intellect (in intuitive science) would not be able to communicate the own author’s system. It is necessary, first of all, the explanation of the third gender of knowledge and its ontological presupposition (substance, attributes and modes). This exposition is possible only by the mediation of Parts I, II, III and IV of the treated work. Posteriorly, is analyzed the imagination as source of a confused knowledge, specifically in Part II. However, we recognize that itself may be a power, as Spinoza notes in proposition XVII of this part. Finally, by superimposing imagination and intuitive science, we inferred as a hypothesis that, ultimately, the power of imagination is in direct bond with the third kind of knowledge. We propose, in the same way, that the intuitive science founds the central idea of ontology in Spinoza (idea of God), from which all the others are deduced, according to the geometric method utilized in Ethics. Such a method founds itself in the intuitive science and makes use of linguistic signals, to communicate systematically the Spinoza’s ontology.